1994
DOI: 10.1590/s0036-46651994000100004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratorial features of visceral toxocariasis in infancy

Abstract: Forty children with a diagnosis of Visceral Toxocariasis were evaluated prospectively from February 1982 to June 1989. Diagnosis was established by clinical, laboratorial and serological (ELISA - ES Toxocara canis antigen) evaluations. A great clinical polymorphism was found in our patients, ranging from unspecific or absent manifestations to an exhuberant symptomatology. The laboratorial findings were: leukocytosis,eosinophilia and elevation of serum gammaglobulin and isohemagglutinin levels. No significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 23 publications
1
14
1
11
Order By: Relevance
“…Covert toxocariasis has been described as presenting non-specific symptoms, such as abdominal pain, headache, cough and limb pains. In some instances, neurological manifestations have been associated with the presence of Toxocara larvae in the brain 9,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Covert toxocariasis has been described as presenting non-specific symptoms, such as abdominal pain, headache, cough and limb pains. In some instances, neurological manifestations have been associated with the presence of Toxocara larvae in the brain 9,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Seroepidemiological studies to detect these antibodies have revealed high prevalence, particularly in children 11,13,19 and are important in patients with a peripheral eosinophilia above 400 eosinophils/mL 11,23 and patients showing clinical symptoms 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Alrededor de 80% de la población estudiada estaba entre los 5 y 44 años de edad. Es decir, la posibilidad de una infección que pueda afectar seriamente la visión puede comprometer la vida productiva de la población, lo cual coincide con otros reportes ( 2,17,20,21,23,25 ).…”
Section: Discussionunclassified
“…Si además consideramos que este problema ha sido reportado principalmente en individuos jóvenes ( 2,6,20,21 ), entonces se hace necesario determinar la verdadera frecuencia de este problema, para que los profesionales médicos de la especialidad sospechen del daño y sobre todo tengan la posibilidad de realizar el diagnóstico adecuado.…”
Section: Introductionunclassified